2020
DOI: 10.1101/2020.06.01.127316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short chain fatty acids enhance expression and activity of the umami taste receptor in enteroendocrine cells via a Gαi/opathway

Abstract: 14The short chain fatty acids (SCFAs) acetate, butyrate and propionate, are produced by the fermentation 15 of non-digestible carbohydrates by the gut microbiota. SCFAs are of interest because they regulate 16 appetite, adiposity, metabolism, glycemic control and immunity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Thus, no evidence is available to suppose that an increased expression of TAS1R1 could interfere with piglet appetite. Interestingly, it has been observed that typical bacterial metabolites, butyrate and propionate, can increase mRNA levels of TAS1R1 and TAS1R3 of intestinal EECs altering their sensitivity to glutamate with a mechanism related to the detection by free fatty acid receptors 2 and 3 [45]. The content of volatile fatty acids in the stomach of our piglets was not measured but it is well known that significant amounts of them can be detected in the gastric content of piglets [46].…”
Section: Discussionmentioning
confidence: 79%
“…Thus, no evidence is available to suppose that an increased expression of TAS1R1 could interfere with piglet appetite. Interestingly, it has been observed that typical bacterial metabolites, butyrate and propionate, can increase mRNA levels of TAS1R1 and TAS1R3 of intestinal EECs altering their sensitivity to glutamate with a mechanism related to the detection by free fatty acid receptors 2 and 3 [45]. The content of volatile fatty acids in the stomach of our piglets was not measured but it is well known that significant amounts of them can be detected in the gastric content of piglets [46].…”
Section: Discussionmentioning
confidence: 79%